EV+A 2001 : expanded. - Barthes, Roland; Burke, Ursula; Byrne, Kate; Carville, Justin; Castro, Jota; Charlesworth, Ian; Colbert, Karen T.; Collins, Anthony; Collins, Phil; Comerford, Oliver; Conroy, Jean; Curran Mulligan, Patricia; et al. (Oysterhaven : Gandon Editions, 2001)
Al-Ani, Jananne ; Bourke, David ; Burke, Ursula ; Byrne, Kate ; Canning, Michael ; Castro, Jota ; Charlesworth, Ian ; Clarke, Jack ; Colbert, Karen T. ; Collins, Anthony ; Collins, Phil ; Comerford, Oliver ; Conroy, Jean ; Curran, Ann Marie ; Curran Mulligan, Patricia ; Daly, Dorothy Ann ; Darby, Angela ; Duffy, Joyce ; Duffy, Rita ; Duggan, Andrew ; Dunne, David ; Emoe, Clodagh ; Farrell, Carissa ; Farrell, Des ; Fitzpatrick, Barry ; Gerrard, John ; Ginnell, Fiona ; Grieg, Nina ; Gunning, Stephen ; Hall, Victoria ; Harris, Pat ; Harty, Catherine ; Hill, Lucy ; Holten, Katie ; Hopkins, Noreen T. ; Hughes, Allan ; Humphries, Tim ; Johnston, Emma Louise ; Jones, Finola ; Jones, Ruth ; Kelly, Catherine ; Kenny, Gillian ; Killane, Helen ; Land Hansen, Karen ; Linehan, Aidan ; McCann, Niamh ; McCarthy, Eoin ; McCrea, Ronan ; McGeorge, Eline ; McGowan, Julie ; McGrath, Dara ; Mackey, Christine ; McNulty, Margo ; McTigue, Eoghan ; MacWilliam, Susan ; Masterson, Caroline ; Moore, Madeline ; Mullarney, Janet ; Mulrooney, Ann ; O'Beim, Aisling ; O'Brien, Treasa ; O'Connell, John ; O'Donoghue, Alice ; O'Donoghue, Augustine ; O'hEocha, Mairead ; O'Kane, Eamon ; O'Mara, David ; O'Reilly, Vanessa ; O'Riordan, Amy ; Peillon, Alice ; Phokela, Johannes ; Potrc, Marjetica ; Pye, Matilda ; Rannou, Catherine ; Redmond, Willie ; Reilly, Ben ; Richards, Peter ; Rush, Cóilin ; Ryan, Gina ; Savage, Peter ; Sedira, Zineb ; Shipsides, Dan ; Slocket, Anne ; Smith, Joan ; Sposati, Camila ; Staunton, Tracy ; Townsin, Sue ; Urata, Kazuyoshi ; Walker, Denise ; Walsh, Brian
biog. per kunstenaar
Engels
EV+A 2001 : expanded. Limerick City Gallery of Art Limerick, 16.03 - 13.05.2001 + volgende locaties in Limerick : No. 8 Pery Square, City Hall, Doswell Print Gallery, Slattery's, Alternative sites
boek